(untitled) (Namibian Journal for Research, Science and Technology, 2024)
This paper presents the findings of a qualitative research study conducted among students at the University of Namibia. The study focuses on the lived experiences of students registered at the University of Namibia regarding their mental health. The study aimed to explore the mental health issues faced by students at the University of Namibia, investigate how students cope with these challenges, and examine the institutional support available to promote students’ mental health. The study adopted a phenomenological design and used a qualitative research approach to gain insight into the experiences of students at the University of Namibia. The participants included 10 students and four key informants, namely a lecturer, a Student Representative Council member, the Dean of Students, and a social worker. The study used exploratory and thematic analysis. The findings were categorised into codes, including stress, COVID-19, negative encounters with lecturers, coping mechanisms, and institutional support. Some participants displayed symptoms of depression, anxiety, and stress, which affected their mental well-being and contributed to poor academic performance.